Fable, Method, and Imagination in Descartes - Griffith, James (Springer International Publishing, 2018)
What role do fables play in Cartesian method and psychology? By looking at Descartes' use of fables, James Griffith suggests there is a fabular logic that runs to the heart of Descartes' philosophy. First focusing on The World and the Discourse on Method, this volume shows that by writing in fable form, Descartes allowed his readers to break from Scholastic methods of philosophizing. With this fable-structure or -logic in mind, the book reexamines the relationship between analysis, synthesis, and inexact sciences; between metaphysics and ethico-political life; and between the imagination, the will, and the passions.